2017
DOI: 10.3389/fpsyg.2017.01809
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles and Adolescents’ School Adjustment: Investigating the Mediating Role of Achievement Goals within the 2 × 2 Framework

Abstract: This study examines the multiple mediating roles of achievement goals based on a 2 × 2 framework of the relationships between parenting styles and adolescents’ school adjustment. The study sample included 1061 Chinese adolescent students (50.4% girls) between the ages of 12 and 19, who completed questionnaires regarding parenting styles (parental autonomy support and psychological control), achievement goals (mastery approach, mastery avoidance, performance approach, and performance avoidance goals) and school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
1
8
2
Order By: Relevance
“…Third, given that authoritative parenting is linked to higher levels of life satisfaction, family interventions and family education program are suggested to employ to improve the practice of authoritative parenting. Moreover, most work on parenting styles has combined maternal and paternal styles (e.g., Xiang et al, 2017 ), or only focused on the effects of maternal parenting styles (e.g., Gherasim et al, 2017 ), whereas the present study showed that, compared with maternal parenting, paternal parenting seemed to play a more important role in Chinese adolescents’ lives, especially in the friend, school, and self domains of life satisfaction. Therefore, intervention programs aiming at promoting adolescent life satisfaction should not only incorporate components related to maternal parenting behaviors, but also pay attention to fathers’ involvement and encourage and cultivate fathers to adopt the authoritative parenting style.…”
Section: Theoretical and Practical Implicationscontrasting
confidence: 76%
See 1 more Smart Citation
“…Third, given that authoritative parenting is linked to higher levels of life satisfaction, family interventions and family education program are suggested to employ to improve the practice of authoritative parenting. Moreover, most work on parenting styles has combined maternal and paternal styles (e.g., Xiang et al, 2017 ), or only focused on the effects of maternal parenting styles (e.g., Gherasim et al, 2017 ), whereas the present study showed that, compared with maternal parenting, paternal parenting seemed to play a more important role in Chinese adolescents’ lives, especially in the friend, school, and self domains of life satisfaction. Therefore, intervention programs aiming at promoting adolescent life satisfaction should not only incorporate components related to maternal parenting behaviors, but also pay attention to fathers’ involvement and encourage and cultivate fathers to adopt the authoritative parenting style.…”
Section: Theoretical and Practical Implicationscontrasting
confidence: 76%
“…For example, in addition to the study by Leung et al (2004) and Xie et al (2016) reported that maternal restrictiveness (also known as demandingness) was negatively associated with Hong Kong adolescents’ family, self, and friend satisfaction 8 months later; and maternal concern (also known as responsiveness) was positively correlated with family, self, and friend satisfaction 8 months later. Xiang et al (2017) reported that parental autonomy support positively predicted adolescents’ life satisfaction, and psychological control negatively predicted adolescents’ life satisfaction. In a longitudinal study with 1 year interval, Shek (2007) found that paternal and maternal psychological control negatively predicted Hong Kong adolescents’ life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…We also operationalized achievement goal orientation as a process variable. This approach is supported by the findings in existing literature on the mediational effects of achievement goal orientation on the link between various input variables and academic-related outcomes (Xiang, Liu, & Bai, 2017).…”
Section: The Present Studymentioning
confidence: 60%
“…In addition to positive supportive parenting, negative parenting characteristics are also associated with academic and developmental outcomes in children and adolescents (e.g., Garcia & Serra, 2019;Sangawi et al, 2018). Negative parenting is not defined merely as an absence of parental support, but rather as different parenting strategies that have potentially detrimental consequences for adolescents (e.g., Xiang et al, 2017). One of the potentially harmful strategies is parental psychological control, which refers to parents' attempts to manipulate and control their children's thoughts and behavior (Barber, 1996).…”
Section: Negative Parenting and Academic Difficultiesmentioning
confidence: 99%